Thickness effect on mechanical behavior of auxetic sintered metal fiber sheets. (5th April 2019) - Zhao, T.F.; Deng, Z.C.; Fu, C.Y.; Wang, X.J.; Zhou, H.Y.; Chen, C.Q.
Abstract: Sintered metal fiber sheets (MFSs) made by sequential-overlap method are transversely isotropic open-cell cellular materials with paper-like fiber network architectures, which exhibit auxeticity and are promising for various potential applications due to the reentrant micro-structure. The thickness effect on the out-of-plane auxeticity (negative Poisson's ratio) of MFSs samples of 2–20 mm thick subjected to in-plane tensile loading is investigated with digital image correlation technique. Furthermore, the deformation modes of fibers within MFSs during various loading stages are examined with X-ray tomography. It is found that in addition to the straightening of reentrant fibers, fiber layers with defects and joints failure induced slippage between adjacent layers leads to local shear and results in unique umbrella-like local deformation termed umbrella effect, which gradually dominates the auxeticity during tensile loading. Although remarkably increasing lateral deformation, the umbrella effect significantly diminishes the in-plane mechanical performance such as rigidity and strength. In particular, this effect is suppressed by sample thickness: the overall performance tends to stabilize with sample thickness greater than a certain value, provided that the MFS is uniform with all fibers randomly distributed. The finding facilitates wider application of auxetic MFSs with further understanding on the relationship between the thickness effect and performance. Graphical abstract: Unlabelled Image Highlights: Reentrant micro-structure of metal fiber sheets is obtained by X-ray tomography, with which Poisson's ratio is predicted. The umbrella effect is found to be another mechanism for auxeticity and dominates deformation with further loading. The umbrella effect significantly diminishes mechanical performance and becomes insensitive beyond a critical thickness. Non-uniform distribution and bundling of fibers cause large auxeticity, but is harmful to mechanical performance.